Electronic structure study of Ce(1-x)A(x)O(2) (A = Zr & Hf) nanoparticles: NEXAFS and EXAFS investigations - Sharma, Aditya; Varshney, Mayora; Shin, Hyun-Joon; Park, Yong Jun; Kim, Min-Gyu; Ha, Tae-Kyun; Chae, Keun Hwa; Gautam, Sanjeev (ROYAL SOC CHEMISTRY, 2014)
Single phase nanoparticles (NPs) of CeO2, Ce0.5Zr0.O-5(2), Ce0.5Hf0.5O2 and Ce0.5Hf0.Zr-25(0).O-25(2) were successfully synthesized by co-precipitation method at constant pH and temperature. The X-ray diffraction results revealed that the additive atoms did not segregate to form secondary phases but led to grain size variation in the NPs. The 10 Dq values in the near edge X-ray absorption fine structure (NEXAFS) spectra at the O K-edge did not vary in the same way as the average grain size was changed for the doped CeO2 NPs. The deconvolution of Ce M-5-edge and detailed analysis of O K pre-edge peak have shown the higher Ce+3/(Ce+3 + Ce+4) ratio in the Zr- and Hf-doped samples. The local atomic structure around the Ce, Zr and Hf atoms was investigated using extended X-ray absorption fine structure (EXAFS) spectroscopy at Ce K-edge, Zr K-edge and Hf L-3-edge, respectively, and the EXAFS data were fitted with the theoretical calculations. The 4f occupancy, Ce+3/(Ce+3 + Ce+4) ratio of Ce ions, coordination number of Ce and Ce-Ce/Ce-O bond distances were sensitive to the additive atoms but not explicitly changed according to the grain size variation in the NPs.
Keywords: DOPED CEO2 NANOPARTICLES; SOLID-SOLUTIONS; RAY; SPECTROSCOPY; OXIDES; STABILITY; CHEMISTRY